Echocardiographic findings in strength- and endurance-trained athletes - Urhausen, A.; Kindermann, W. (International Journal of Sports Medicine, 1992)
Assessment of echocardiographic measurements in athletes should take into account the specific sport and the quantity and quality of training. In addition, values corrected for body dimensions, especially the active body mass, should be used rather than absolute values. All parts of the athlete's heart are enlarged and its performance increases. Highly trained endurance athletes show the most enlarged hearts. Athlete's heart can be observed in athletes of all ages including the young. However, it is rarer than generally assumed. To differentiate between physiological and pathological myocardial changes, the relationship between heart size and ergometric performance as well as the echocardiographically measured ratio between left ventricular (LV) myocardial thickness and volume are useful; the latter remains unchanged, on the whole, in endurance- and strength-trained athletes. Concentric hypertrophy cannot be induced by strength training alone; additional factors, such as hypertension, aortic stenosis, cardiomyopathy or anabolic steroid use can play an important role. When corrected for body dimensions, non-endurance-trained, e.g. strength-trained, athletes have standard heart sizes even if considerable time is devoted to training. Findings in healthy untrained persons with large body dimensions also indicate no significant difference between the increase of echocardiographic measures caused by training and that caused by growth. An LV myocardial thickness of 13mm is seldom exceeded even in the highly endurance-trained or anabolic drug-free strength trained athletes under physiological conditions. However, the echocardiographic differentiation of cardiomyopathy can be difficult if an individual is highly trained and has large body dimensions. In such cases, LV end-diastolic diameter may be up to 66 to 70mm. The upper normal value of LV muscle mass is 170 g/m2 for a physiological heart enlargement. Future areas of ivestigation should include: adaptative changes of the right ventricle; differences in the regression of the athlete's heart after cessation of training; the differentiation between echocardiographic changes in highly endurance-trained or combined strength-endurance-trained persons and pathological changes; the importance of heart size and endurance sports performance; and finally the influence of genetic factors.